Modified Convective Stratiform Technique (CSTm) Performance on Rainfall Estimation in Indonesia - E. Endarwin; Safwan Hadi; Bayong Tjasyono HK; Dodo Gunawan; S. Siswanto (Journal of Mathematical and Fundamental Sciences, 2014)
This study has analyzed a rainfall estimation using a modified convective stratiform technique (CSTm). Unlike the original convective stratiform technique (CST), which only utilizes infrared (IR) data, CSTm applies not only IR data but also passive microwave (PMW) data. Two major modifications contained in CSTm are: (1) the application of a variability index (VI) method that uses PMW data to perform convective and stratiform separation,and (2) the ability to determine the average extensive coverage of the new areas of each pixel point as a result of the utilization of the PMW data. In this study, rainfall estimation was conducted for 23 points spread over four major islands in Indonesia. The estimation was performed based only on IR and PMW data obtained from coincident observations. For verification, the estimation results were compared with real observations. The main verification action conducted in this study used multi-category contingency tables for four categories and this action was supported by the root mean square error (RMSE)method.The verification results of the hourly estimation conducted for 4 days in early November 2011 showed that CSTm can effectively improve the performance quality of CST.